Monitoramento da altura de lâmina de água de irrigação na lavoura de arroz - (:unkn) unknown (Universidade Federal do Pampa, 2015)
Rice (Oryza sativa L.) is part of the staple food for about 3 billion people in the world and is cultivated in 116 countries. This cereal is produced in all Brazilian states, however, the bulk of domestic production is concentrated in the states of Rio Grande do Sul and Santa Catarina. In this region are the conventional tillage, minimum and pre -germinated system, both with different heights of water depth and thus rising questions to be researched on the income components relating to culture. Thus, the objective of this study was to monitor the height of the irrigation water depth and its interference in yield components of irrigated rice. The experimental design was randomized blocks (four blocks) pro five treatments compounds, which are consisting of the following heights of water depths: 2.5 cm; 5.0 cm; 7.0 cm; Greater than 10 cm and 10 cm. We evaluated the number of plants per meter, number of tillers per meter, and the water temperature manually. The results showed that interference is at least five variables briefly evaluated at IRGA -417, and with a high environmental variability . Populations of plants per meter, tiller number per meter at forty days are not affected, but the tillers per plant per meter have superiority in 7 blade height and 5 cm. There tiller reduction of forty to sixty days and the water temperature has decreased in the blade height of 10 cm and greater than 10 hours in the 15 and 16 hours.
Keywords: Oryza sativa L.; Sistemas de cultivo; Altura de lâmina; Growing systems; Blade height; CNPQ::CIENCIAS AGRARIAS